Initial experience of a novel method for electrical isolation of the superior vena cava using cryoballoon in patients with atrial fibrillation. Issue 2 (20th November 2022) - Lin, Changjian; Bao, Yangyang; Xie, Yun; Wei, Yue; Luo, Qingzhi; Ling, Tianyou; Zhang, Ning; Jin, Qi; Pan, Wenqi; Xie, Yucai; Wu, Liqun
Abstract: Background: Damage to the sinus node (SN) has been described as a potential complication of superior vena cava (SVC) isolation. There have been reports of permanent SN injury requiring pacemaker implantation during isolation of the SVC. Hypothesis: It is safe and effective to isolate SVC with the second‐generation 28‐mm cryoballoon by using a novel method. Methods: Forty‐three patients (including six redo cases) with SVC‐related atrial fibrillation (AF) from a consecutive series of 650 patients who underwent cryoballoon ablation were included. After pulmonary vein isolation was achieved, if the SVC trigger was identified, the SVC was electrically isolated using the cryoballoon. First, the cryoballoon was inflated in the right atrium (RA) and advanced towards the SVC‐RA junction. After total occlusion was confirmed by dye injection with total retention of contrast in the SVC, the SVC‐RA junction was determined. Next, the cryoballoon was deflated, advanced into SVC, then reinflated, and pulled back gently. The equatorial band of the cryoballoon was then set slightly (4.32 ± 0.71 mm) above the SVC‐RA junction for isolation of the SVC. Results: Real‐time SVC potential was observed in all patients during ablation. The mean time to isolation was 24.5 ± 10.7 s. The SVC was successfully isolated in all patients. The mean number of freeze cycles was 2.5 ± 1.4 per patient, and the mean ablation time was 99.8 ± 22.7 s. A transient phrenic nerve (PN) injury occurred in one patient (2.33%). There were no SN injuries. Freedom from AF rates at 6 and 12 months was 97.7% and 93.0%, respectively. Conclusions: This novel method for SVC isolation using the cryoballoon is safe and feasible when the SVC driver during AF is determined and could avoid SN injury. PN function should still be carefully monitored during an SVC isolation procedure.